2021
DOI: 10.3390/jpm11050366
|View full text |Cite
|
Sign up to set email alerts
|

An Association Rule Mining Analysis of Lifestyle Behavioral Risk Factors in Cancer Survivors with High Cardiovascular Disease Risk

Abstract: We aimed to assess which lifestyle risk behaviors have the greatest influence on the risk of cardiovascular disease in cancer survivors and which of these behaviors are most prominently clustered in cancer survivors, using logistic regression and association rule mining (ARM). We analyzed a consecutive series of 897 cancer survivors from the Korean National Health and Nutritional Exam Survey (2012–2016). Cardiovascular disease risks were assessed using the atherosclerotic cardiovascular disease score (ASCVDs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In the current study, AYA survivors were significantly more likely to be current or former smokers than controls, similar to previous findings that AYA survivors are more likely to smoke than the general population 43 . It has also been shown that AYA survivors with chronic health conditions are more likely to smoke than AYAs without chronic health conditions and that smoking co‐occurs with other modifiable CVD risk factors in cancer survivors 44,45 . Taken together with our findings that AYA survivors who are current or former smokers have close to twice the odds of CVD as those who never smoked, interventions aimed at smoking cessation and prevention are needed in this population.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, AYA survivors were significantly more likely to be current or former smokers than controls, similar to previous findings that AYA survivors are more likely to smoke than the general population 43 . It has also been shown that AYA survivors with chronic health conditions are more likely to smoke than AYAs without chronic health conditions and that smoking co‐occurs with other modifiable CVD risk factors in cancer survivors 44,45 . Taken together with our findings that AYA survivors who are current or former smokers have close to twice the odds of CVD as those who never smoked, interventions aimed at smoking cessation and prevention are needed in this population.…”
Section: Discussionsupporting
confidence: 90%
“…Factors such as high aspartate aminotransferase and high serum sodium were identified as significant rules showing a strong association with cognitive decline. In addition, ARM can specify which non-hierarchical phenotype has been achieved by effective clustering of multiple diseases [40][41][42]. However, ARM usually deals with Boolean data, so it is difficult to analyze associations among the numerical data.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, association rule mining was used in market basket analysis (MBA) techniques, which functioned to analyze consumer buying patterns in a supermarket [28]; for example, if a consumer buys bread, he usually buys milk. Currently, MBA is used in other sectors, such as the health sector [29][30] and socio-economics [31].…”
Section: Association Rule Miningmentioning
confidence: 99%